The Role of Social Media in Improving the Marketing Performance of SMEs - Hartiani, Hartiani; Zainuddin, Muhammad; Rahadi, Irwan (Fakultas Ekonomi, UIN Maliki Malang, 2025)
Small and Medium Enterprises (SMEs) in Lombok, West Nusa Tenggara, are vital to the region’s economy but continue to underutilize social media as a strategic marketing tool. This study investigates the impact of social media usage on marketing performance among SMEs, with a specific focus on the mediating role of marketing capabilities. Adopting a quantitative cross-sectional design, the research surveyed 179 food and beverage processing SMEs selected via stratified random sampling. Data were collected using a structured 5-point Likert questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. Findings reveal that social media usage significantly enhances marketing capabilities. Marketing capabilities significantly improve marketing performance. Social media has a direct positive effect on marketing performance. Marketing capabilities significantly mediate the relationship between social media and marketing performance. These results emphasize that marketing performance benefits more from capability development than from direct media usage. Social media serves as a strategic driver of SME marketing performance, particularly when coupled with strong marketing capabilities. Policymakers and SME practitioners are encouraged to prioritize digital training programs that strengthen strategic marketing competencies.